A Survey-Based Assessment of "Matter of Balance" Participant Fall-Related Experience. Issue 5 (September 2021) - Valatka, Robin; Krizo, Jessica; Mallat, Ali
Abstract : Background: Falls are a substantial cause of injury in older adults, which can be attributed to progressive lack of physical activity, associated comorbidities, social isolation, and chronic health conditions. Fall prevention courses are designed to educate participants on fall safety and increase activity levels and social engagement. Objective: The purpose of this study was to evaluate the perceived effectiveness of a nationally recognized fall prevention course on self-reported fall frequency and lifestyle habits. Methods: This was a single-group pretest–posttest study of a convenience sample of older adults enrolled in a group fall prevention program, A Matter of Balance, in a community setting between March 2019 and March 2020. Questionnaires were distributed at the first and final sessions of the course to evaluate participant perceptions of the program and its impact on their fall history, exercise habits, and social engagement. Comparisons were made using Wilcoxon rank sum tests. Results: A total of 40 class members agreed to participate, with 29 (73%) completing both the presurvey and the postsurvey. Responses indicated no change in the number of falls or participants following an established exercise routine. However, of those who fell prior to the course, 75% reported a reduction in falls. In addition, the participants reported an overall increase in weekly exercise frequency. In those who reported fear of falling, 71% reported a reduction in fear following the course. Conclusions: The participants in this study self-reported a decrease in fall rate, a decrease in fear of falling, and an increase in exercise frequency. The course is not fall protective but can be considered an adjunct to fall prevention measures that include medical, medication, visual, and environmental management.